2014
DOI: 10.1111/flan.12099
|View full text |Cite
|
Sign up to set email alerts
|

The Undergraduate Spanish Major Curriculum: Realities and Faculty Perceptions

Abstract: This article presents the quantitative and qualitative results of a nationwide survey of Spanish department faculty on the components of their undergraduate Spanish major curriculum and their perceptions of these components, as well as their perceptions of recent Modern Language Association (MLA) reports (2007, 2009) and the reports' influence on curricular change in their programs. Results indicate that, while institutions required and offered a wide variety of courses, literature courses composed the core of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Nearly half of the respondents reported that literature was their main area of expertise (50), followed by linguistics/applied linguistics (26), generalist or other (15), language (8), and culture (5). See Hertel and Dings () for further details regarding the distribution of faculty based on years of experience, rank, and area of expertise among different institution types.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly half of the respondents reported that literature was their main area of expertise (50), followed by linguistics/applied linguistics (26), generalist or other (15), language (8), and culture (5). See Hertel and Dings () for further details regarding the distribution of faculty based on years of experience, rank, and area of expertise among different institution types.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reporting the survey results of faculty from around the United States (Hertel & Dings, ) found that within the previous 5 years, although the majority of Spanish undergraduate curricula still focused heavily on literature at the advanced undergraduate level, this emphasis had begun to change. Specifically, 16% of the faculty indicated that their department's Spanish undergraduate major curriculum had changed significantly, 62% indicated that it had changed somewhat, 19% noted that it had not changed, and 3% answered that they did not know (p. 533).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations